The Continuing Value of Harry Braverman's Labor and Monopoly Capital. Issue 1 (1st September 2022) - Carter, Bob; Choonara, Joseph
Abstract : Harry Braverman's Labor and Monopoly Capital (1974) was widely acknowledged to be a significant intervention in the debate on the political economy of work within contemporary capitalist societies. Despite the radicalism of some initial contributors, over time a new orthodoxy hostile to the Marxist foundation of Braverman's work was established so that today his influence has waned. His legacy is largely restricted to a simplified and linear theory of the labour process, with the focus that work under capitalism is subject to a dynamic of deskilling. The richness of Braverman's contribution and observations on issues of political economy, such as the separation of ownership and control, class relations, and the reserve army of labour, subjects of initial discussion and criticism, are ignored. The paper summarizes the major themes in Braverman's work, and challenges many of the criticisms made since its publication. It also discusses some limitations, including those deriving from Braverman's complex relation to Paul Baran and Paul Sweezy's political economy, confusion regarding the position of the 'middle layers' within employment, and the absence of a sufficiently nuanced account of labour markets. Finally, it addresses some of the changes to capitalism since Braverman's day, arguing that contemporary labour processes can be best explored through an engagement with his pioneering work.